2017
DOI: 10.1115/1.4037187
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Assessment of Microwave Ablation for Treating Esophageal Varices

Abstract: Esophageal varices are a significant complication of portal hypertension. Endoscopic variceal ligation (EVL) is one of the clinical standards for treating these varices and preventing their hemorrhage. Limitations of EVL include the risk of stricture formation and postband ulcer bleeding due to the damage caused to the esophageal mucosa, as well as the need for multiple endoscopic treatment sessions to eradicate the varices. The goal of this study is to develop a device and evaluate the technical feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, a directional heating pattern may be required for some specific scenarios where, for example, a target tumor is close to the bowel which should not be ablated. Different types of MWA antennas with directional heating patterns have been developed and reported [259]- [261].…”
Section: Emerging Bioelectromagnetics Applications a Microwave Ablationmentioning
confidence: 99%
“…However, a directional heating pattern may be required for some specific scenarios where, for example, a target tumor is close to the bowel which should not be ablated. Different types of MWA antennas with directional heating patterns have been developed and reported [259]- [261].…”
Section: Emerging Bioelectromagnetics Applications a Microwave Ablationmentioning
confidence: 99%
“…Sebek et al 9 integrated a modified version of the directional device of McWilliams et al 21 shown in Fig. 13a into a standard endoscopic cap for the application of treating esophageal varices (see Fig.…”
Section: Mw Ablation Applicatorsmentioning
confidence: 99%
“…Examples of technologies for delivering ablative energy via (A) percutaneous, (B) intracavitary (adapted from Burtnyk et al 8 ), (C) endovascular (adapted from Fernández-Ruiz 10 ), (D) endoscopic approaches (adapted from Sebek et al 9 ).…”
Section: Figmentioning
confidence: 99%